Solid fuel use, socioeconomic status and depression: a cross-study of older adults in China - Ying Duan; Zihao Liu; Qi Qi; Huaqing Liu; Min Zhang (BMC Geriatrics, 2024)
Abstract Background Indoor air pollution causes severe psychological stress and promotes depression. A better understanding of the impact of solid fuel consumption and socioeconomic indicators on mental health is critical to promote successful aging. In this study, we analyzed the relationship of depression with socioeconomic status (SES) and solid fuel use, and illustrated the mediating role of solid fuel use in the relationship between SES and depression. Methods 9250 participants from the 2018 wave of the Chinese Longitudinal Healthy Longevity Survey were included in this study. A logistic regression analysis was used to calculate odds ratio (OR) and 95% confidence interval (CI) of depression for different types of fuel consumption. The stepwise approach and the Sobel test were used to test the mediation effect. Results Older people who reported the consumption of solid fuels showed higher odds of having depressive symptoms (OR = 1.16, 95% CI:1.03, 1.31). In model with depression as the outcome variable, the ORs of low education level and low annual household income level were 1.30 (95% CI: 1.15, 1.47) and 1.43 (95% CI: 1.28, 1.59) respectively. Solid fuel consumption accounted for 38.40% of the effect of a low education level and 54.73% of the effect of low income on depression. Conclusions Solid fuel use and SES are associated with depression, and solid fuel use may act as a potential mediator connecting socioeconomic indicators and depression.